Kedudukan Eigendom Verponding Dalam Hukum Pertanahan Di Indonesia - Liadi, William Seven (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2019)
The issue of land disputes in Indonesia has been increasing lately, especially inrights Eigendom's. This is indicated by the many cases of disputes over land parcels. The results showed that theright should Eigendom Verponding no longer be enforced in Indonesia considering that the Eigendom Verponding right itself was one of the products of land law during the Dutch colonial era in Indonesia. This research is a normative law research by reviewing materials derived from legislation and literature. The approach used in this study is the conceptual approach and statute approach. The results of this study are Eigendom Verponding rights which should berights holders Eigendom Verponding must convert their land to SHM with a time limit until 1980. But the position of Eigendom Verponding in Indonesia is still valid and can be changed to SHM